Electro co-deposition of Ni-A12O3 composite coatings - Corni, Ilaria; Chater, Richard J.; Boccaccini, Aldo R.; Ryan, Mary P. (Journal of Materials Science, 2012)
Nickel-Al O composite coatings have been successfully deposited galvanostatically on to stainless steel substrates by electro co-deposition from a Watts bath containing between 50 and 150 g/l of sub-micron or nanosized alumina particles applying current density of -10, -20 and -32 mA cm-2. The alumina distribution in the composite films on the two sides of the substrate was remarkably different due to solution hydrodynamics and electric field effects. The effect of current density, particle concentration in the bath and particle size are studied systematically producing a comprehensive set of data for better understanding the effects of these variables on the amount of particles co-deposited. The amount of Al O co-deposited in the films increases with the particle concentration in the bath and strongly depends on the current density and on particle size. The effect of the current density and of the alumina inclusions on the crystallinity of the Ni matrix and on the Ni crystallites grain size has also been studied. The inclusions of nano or sub-micron-Al O particles are found to strongly influence the metallic nickel microstructure. © 2012 Springer Science+Business Media, LLC.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.electr_3